A budget impact analysis of gilteritinib for the treatment of relapsed or refractory FLT3mut+ acute myeloid leukemia in a US health plan. (1st January 2021) - Pandya, Bhavik J.; Yang, Hongbo; Schmeichel, Cynthia; Qi, Cynthia Z.; Shah, Manasee V.
Abstract: Aims: To estimate the economic impact of the introduction of gilteritinib for the treatment of relapsed/refractory (R/R) FLT3 mutation-positive ( FLT3 mut+ ) acute myeloid leukemia (AML) from a US payerâ€™s perspective. Methods: A budget impact model (BIM) was developed to evaluate the 3-year total budgetary impact of treating adults with R/R FLT3 mut+ AML eligible for gilteritinib in a hypothetical US health plan. Total costs (drugs/administration, hospitalization, monitoring, adverse events, transfusions, subsequent hematopoietic stem cell transplantation, post-progression, and FLT3 testing) were estimated before and after gilteritinib entry. The budget impact was the total cost difference between the two scenarios. The target population size and cost inputs were based on public data or published literature, drug market share was informed by market research data, and the model included recommended treatments for R/R FLT3 mut+ AML per clinical guidelines. Deterministic sensitivity analyses (DSAs) and scenario analyses varying key model inputs and assumptions were conducted to test for robustness. Results: In a hypothetical health plan with 1 million members, 20.9 adults with R/R FLT3 mut+ AML were estimated to be eligible for gilteritinib. Of these, it was assumed 30.0% would be treated with gilteritinib in Year 1 following gilteritinib entry, increasing the total plan budget by $663, 795 and the per-member-per-month (PMPM) cost by $0.055. In Years 2â€"3, the market share of gilteritinib increased to 45.0%, increasing the total plan budget impact by $1, 078, 371 and $1, 087, 230, and the PMPM cost by $0.090 and $0.091, respectively. The model results remained robust in DSAs and scenario analyses, with the largest impact observed when the projected uptake of gilteritinib was changed. Limitations: The results of this BIM are contingent upon the modelâ€™s assumptions and inputs. Conclusions: Adding gilteritinib to the formulary for the treatment of adults with R/R FLT3 mut+ AML had a minimal budget impact from a US payerâ€™s perspective.